The Effect of Application of Experiment Method with STEAM Approach on Science Learning Outcomes in Elementary School Students - Putri, Anindita Historiana; Azizah, Diva Agistia Nur; Sari, Dinda Putri Rahmanda; Qudsyi, Sholita Amirah; Setiawan, Ricky (research, training and philanthropy institution Natural Aceh, 2025)
This study intends to analyze the impact of applying the experimental method with the Science, Technology, Engineering, Art dan Math (STEAM) approach on the learning outcomes of science on the material of electrical energy sources for class VB students at SDN Panjunan Sidoarjo. This study uses a quantitative approach with a pre-experimental design type called a one-group pre-test-post-test design. The study sample consisted of 19 students. Data were collected using tests and analyzed using parametric statistical tests paired t-tests with normality tests as prerequisite tests. The average pre-test score was 57.63, while the average post-test score was 76.68. Through the paired t-test, the results were obtained in the form of an asymp value. Sig (2-tailed) 0.000 (less than 0.05), so it can be concluded that applying the experimental method with the STEAM approach affects the learning outcomes of class V students at SDN Panjunan Sidoarjo. Thus, evidence was obtained that using experimental methods with the STEAM approach in science learning activities significantly contributed to optimizing science education outcomes for elementary students because it actively involved students in gaining meaningful experiences.